Practice-Based Research in Three Personal Turns - Tucker, Sherrie (Performance Matters, 2023)
In this contribution to the forum on Practice-Based Research (PBR), the author reflects on PBR "moves" throughout her career, identifying three moments when she could feel her practice change, in very personal and embodied ways. She reflects on the "personal turns" and the unanticipated methods and information that emerged.